Αξιοποίηση πλατφόρμας ηλεκτρονικής μάθησης σε πρόγραμμα 1:1 (ένας μαθητής, μια συσκευή) στην Κυπριακή Δημοτική Εκπαίδευση - Ονουφρίου, Ειρήνη (Department of Communication and Internet Studies, Faculty of Communication and Media Studies, Cyprus University of Technology, 2015)
This dissertation studies the e-learning platform 1:1 which is used at specific Primary School.
Keywords: E-learning platform; Primary education; Δημοτική εκπαίδευση; Κύπρος; Πλατφόρμα ηλεκτρονικής μάθησης